1994
DOI: 10.1111/j.1365-2893.1994.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective detection of human hepatitis B virus surface and core antigens in peripheral blood mononuclear cell subsets by flow cytometry

Abstract: The presence of hepatitis B surface protein (HBs) and hepatitis B core protein (HBc) was investigated, by flow cytometry, on the surface of peripheral mononuclear cells (PBMC) from cells of the following phenotype: CD3 (T lymphocytes), CD4 (T helper/ inducer), CD8 (T cytotoxic/suppressor), CD19 (B lymphocytes) and CD56 [natural killer (NK) cells] among eight patients suffering from chronic hepatitis B and five healthy HBV-negative subjects. This study demonstrated the presence of HBsAg and HBcAg on the lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…In one study, 35 patients with HBV chronic active hepatitis and 38 out of 60 patients with acute hepatitis B (63%) expressed HbsAg in PBMC. In another work, Chemin et al demonstrated the selective detection of HBsAg and HBcAg on B lymphocytes and natural killer cells from chronically HBV-infected patients (52). Hepatitis C virus (HCV), woodchuck hepatitis virus, and varicella-zoster virus were also detected by FCM in PBMCs using monoclonal antibodies to HCV core antigen (34), polyclonal antibodies to woodchuck hepatitis virus (51), and antibodies to the gpI glycoprotein from varicella-zoster virus (296), respectively.…”
Section: Cd38mentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, 35 patients with HBV chronic active hepatitis and 38 out of 60 patients with acute hepatitis B (63%) expressed HbsAg in PBMC. In another work, Chemin et al demonstrated the selective detection of HBsAg and HBcAg on B lymphocytes and natural killer cells from chronically HBV-infected patients (52). Hepatitis C virus (HCV), woodchuck hepatitis virus, and varicella-zoster virus were also detected by FCM in PBMCs using monoclonal antibodies to HCV core antigen (34), polyclonal antibodies to woodchuck hepatitis virus (51), and antibodies to the gpI glycoprotein from varicella-zoster virus (296), respectively.…”
Section: Cd38mentioning
confidence: 99%
“…Quantitative and dynamic analyses of hepatitis virus markers are important in the follow-up of antiviral treatments (32). HBV surface (HBsAg) and HBV core (HbcAg) antigens in peripheral blood mononuclear cells (PBMCs) from HBV patients have been detected by FCM using antibodies (52,278). In one study, 35 patients with HBV chronic active hepatitis and 38 out of 60 patients with acute hepatitis B (63%) expressed HbsAg in PBMC.…”
Section: Cd38mentioning
confidence: 99%
“…A mérések egyaránt információt nyújtanak a fertőzött sejtek típusáról és arányáról, valamint a megjelenített antigének mennyiségének detektá-lása révén a fertőzöttség mértékéről is. Számos vírus-diagnosztikában használható FACS-módszert validáltak már klinikai mintákban, például a humán immundeficientia vírus (HIV), cytomegalovirus (CMV) [19], humán T-lymphotrophic vírus I és II (HTLV I és II) [20], humán herpeszvírusok [21], Epstein-Barr-vírus (EBV) [22], varicella zoster [23], hepatitis B-vírus (HBV) [24], hepatitis C-vírus (HCV) [25], rabies [26] stb. Klinikai jelentősége miatt részletesebben a CMVés a HIV-fertőzés áramlási citometriával történő kimutatását mutatom be.…”
Section: áBraunclassified
“…One of the mechanisms of viral immune evasion, frequently utilized by viruses capable of long-term persistence, is their ability to infect immune cells (Alacami & Koszinowski, 2000). The lymphotropic nature of HBV has been shown in both in vivo and in vitro conditions (Korba et al, 1987;Blum et al, 1991;Chemin et al, 1992;Calmus et al, 1994;Bläckberg & Kigg-Ljunggren, 2001;reviewed in Michalak 2000;Michalak et al, 2007;Pontisso et al, 2008;Coffin et al, 2011aCoffin et al, , 2011b. On the other hand, the ability of WHV, which is a close relative of HBV, to infect and propagate in cells of the immune system has been well documented (Korba et al, 1988;Michalak et al, 1999;Michalak et al, 2004Michalak et al, , 2007; reviewed in Michalak 2000Michalak , 2004.…”
Section: Hbv and Its Pathological Significancementioning
confidence: 99%
“…It is now evident that the anti-viral immunity established after an encounter with WHV or HBV at doses that cause hepatitis is not able to completely eradicate the virus and replication of virus persists in both hepatocytes and cells of the lymphatic system (Chemin et al, 1992(Chemin et al, , 1993Michalak et al, , 1999Cabrerizo et al, 2000;Mulrooney & Michalak, 2003;Murakami et al, 2004). In this form of infection, the virus can persist for many years without apparent variations in its sequence or emergence of cell typespecific mutants (Laskus et al, 1999;Bläckberg & Kidd-Ljunggren, 2001;Mulrooney-Cousins & Michalak, 2008).…”
Section: Secondary Occult Hepadnaviral Infectionmentioning
confidence: 99%